Screening of tenuazonic acid production-inducing compounds and identification of NPD938 as a regulator of fungal secondary metabolism. Issue 10 (11th August 2021) - Motoyama, Takayuki; Ishii, Tomoaki; Kamakura, Takashi; Osada, Hiroyuki
ABSTRACT: The control of secondary metabolism in fungi is essential for the regulation of various cellular functions. In this study, we searched the RIKEN Natural Products Depository (NPDepo) chemical library for inducers of tenuazonic acid (TeA) production in the rice blast fungus Pyricularia oryzae and identified NPD938. NPD938 transcriptionally induced TeA production. We explored the mode of action of NPD938 and observed that this compound enhanced TeA production via LAE1, a global regulator of fungal secondary metabolism. NPD938 could also induce production of terpendoles and pyridoxatins in Tolypocladium album RK99-F33. Terpendole production was induced transcriptionally. We identified the pyridoxatin biosynthetic gene cluster among transcriptionally induced secondary metabolite biosynthetic gene clusters. Therefore, NPD938 is useful for the control of fungal secondary metabolism. Graphical Abstract: